Surface coating of spinel LiMn2O4 cathode electrode with lithium-nickel-manganese-oxide by RF sputtering method for lithium-ion batteries - Chae, Yujin; Lee, Joong Kee; Choi, Wonchang (ELSEVIER SCIENCE SA, 2014)
Lithium-nickel-manganese-oxide was coated using sputtering equipment on spinel LiMn2O4 cathode electrodes prepared by a conventional tape-casting method. Surface modification of the electrodes was confirmed by field emission scanning electron microscopy and field-emission electron-probe microanalysis. Electrochemical evaluations were performed in constant current mode and the galvanostatic intermittent titration technique revealed that surface coating improved the rate capability of electrode in lithium cells. The surface-modified electrode exhibited better capacity retention and suppressed the impedance increase during the storage test at 60 degrees C in a fully charged state as compared to the bare electrode. Also, the lithium-nickel-manganese-oxide deposition improves the thermal stability of electrodes as confirmed by differential scanning calorimetry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DISSOLUTION